Development of Virtual Reality Learning Media Based on the Kuula Platform Assisted by ClassPoint on Fluid Material to Improve Cognitive Learning Outcomes of Grade XI High School Students - Mohammad Qais Rezvani; Sultan Hammad Alshammari; Rince Aida Rostika; Eko Risdianto; Bodi Gunawan; Mageswaran Sanmugam (FINGER : Jurnal Ilmiah Teknologi Pendidikan, 2026)
Background: The rapid advancement of ICT (information and communication technology) during the Fourth Industrial Revolution offers great potential to transform physics learning, especially for abstract topics such as fluid matter. Limited laboratory facilities and suboptimal learning schedules in many schools can hinder students' understanding and cognitive learning outcomes.Objectives: This research seeks to: (1) ascertain the viability of the developed media, (2) measure the improvement in high school students' cognitive learning outcomes, and (3) determine students' responses to the learning media.Method: The ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) was used in this research and development (R&D) study. The learning media developed was a 360° Virtual Reality video based on the Kuula platform integrated with ClassPoint. The trial was conducted on 39 eleventh-grade students utilizing a pretest-posttest approach in a single group. Data were collected through media and subject matter expert validation sheets, cognitive learning outcome tests, and questionnaires for student responses. Validation and student response data were subjected to descriptive and quantitatively analysis, while improvements in cognitive learning outcomes were analyzed using N-Gain scores.Results: Expert validation produced an average feasibility score of 90.16% (highly feasible). Students' cognitive learning outcomes improved significantly, with a high category N-Gain score of 0.83. The media received a highly favorable response from students, with an average score of 91.37% (very good).Conclusion: The virtual reality learning media based on the Kuula platform assisted by ClassPoint that was developed was declared highly feasible and effective in raising high school students’ cognitive learning outcomes on fluid material, particularly Archimedes' Principle. This media is an innovative alternative for schools with limited laboratory facilities.